CZECH ACADEMIC ETIQUETTE - Hanzelinova, Lada (PEOPLE: International Journal of Social Sciences, 2019)
Although the academic etiquette is daily applied in the world of academia and international conferences, it still remains a largely uncharted territory. Some coded rules emerged with the establishment of first universities in the 12th century; at present, some specific rules are directly stipulated by law, some are governed by university statutes, but many of these rules are customary-law practices. The aim of the present study is to try to define the areas where academic etiquette is applicable and determine their three basic aspects: establishing contact, image and common communication. Detailed attention will be paid to the first aspect dealing primarily with the ways of indicating hierarchy through titles and ranks in the Czech academic world, which currently differs from other Central European countries, although stemming from the same tradition.